PERAN TRICHOKOMPOS DAN PUPUK NPK 16-16-16 TERHADAP SERAPAN DAN RESIDU HARA N DAN P, SERTA HASIL JAGUNG KETAN (Zea mays ceratina) - Yulia Nuraini; Muzna Aqila (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Waxy corn still has a low yield potential. The application of NPK 16-16-16 and compost enriched with Trichoderma sp. fungus or Trichocompost can be a solution. This study aims to determinate the role of Trichocompost and NPK 16-16-16 fertilizer on N and P uptake and residues, and waxy corn yield. Research was conducted using randomized block design consisting of 6 treatments, namely (1) TN0 (Control Without Fertilizer), (2) TN1 (NPK Control), (3) TN2 (Trichocompost 2 t ha-1 + NPK 50%), (4) TN3 (Trichocompst 2 t ha-1 + NPK 75%), (5) TN4 (Trichocompost 3 t ha-1 + NPK 50%) and (6) TN5 (Trichocompost 3 t ha-1 + NPK 75%). The parameters observed is N and P nutrient uptakes and residues, and waxy corn yield that consisted of fresh weigh of cob with cornhusk, fresh weigh of cob without cornhusk and length of cob. The results showed that Trichocompost and NPK 16-16-16 significantly affected N and P nutrient uptake, the highest effect was found in TN5, which was 1,57 g plant-1 N danÂ 7,76 g plant-1 P. Residues of N and P that left in the soil due to TN5 treatment were also classified as high, which was 0.8% N and 95.2 ppm P. Application of Trichocompost and NPK 16-16-16 fertilizer in TN5 also showed the best yield on waxy corn, which was 202 g plant-1 fresh weigh of cob with cornhusk, 180,7 g plant-1 fresh weight of cob without cornhusk and length of cob 18,6 cm.